Pembagian Harta Warisan Secara Adat Masyarakat Muslim Talaud - Risnayani Lahinda (IAIN Manado, 2023)
This article aims to describe the division of the inheritance of the Talaud Muslim community and analyze it in Islamic law. This research is qualitative research using inductive analysis. Results found that boys and girls get the same amount. This distribution of assets is also carried out when the parents are still alive. In addition, the gift of property applies to adopted children and stepchildren. Debts in the distribution of inheritance are the responsibility of all children when their parents die. If viewed from an Islamic point of view, sharing assets equally between boys and girls is permissible as long as it does not harm one of the parties and must be voluntary; the distribution of inheritance before the heir dies can be done with grants. There is no prohibition on giving estate in takharuj, which is obligatory for adopted children or stepchildren. Finally, the settlement of debt cases where Islam strongly recommends immediately resolving these debt problems because they relate to other people's rights. Keywords: Inheritance Custom; Fiqh Mawaris; Muslim Community. ABSTRAKArtikel ini bertujuan untuk mendeskripsikan pembagian harta warisan masyarakat Muslim Talaud dan menganalisisnya dalam Hukum Islam. Penelitian ini merupakan penelitian kualitatif dengan menggunakan analisis induktif. Hasil yang ditemukan adalah anak laki-laki maupun perempuan mendapatkan jumlah yang sama. Pembagian harta ini juga dilakukan saat orang tua masih hidup. Selain itu, pemberian harta berlaku untuk anak angkat dan anak tiri. Hutang-piutang dalam hal pembagian harta warisan menjadi tanggungjawab semua anak saat orang tua meninggal. Jika dilihat dari kacamata Islam membagikan harta secara sama rata antara anak laki-laki dan perempuan itu boleh asalkan tidak merugikan salah satu pihak dan harus secara sukarela, pembagian harta warisan sebelum pewaris meninggal dapat dilakukan dengan hibah dan tidak ada larangan untuk memberi harta warisan dalam bentuk takharuj wajibah kepada anak angkat ataupun anak tiri. Terakhir, penyelesaian perkara hutang yang dimana Islam sangat menganjurkan untuk segera menyelesaikan permasalahan hutang-piutang ini karena bersangkutan dengan hak orang lain.